Awareness and management of endocrinologists from the Philippines on the interrelationship between diabetes and periodontal disease - Quintos, Francheska Martina R.; Quintos, Francheska Martina R.; Zara, Patricia Mae M.
Objective: To determine the awareness on the interrelationship between diabetes and periodontal disease among endocrinologists from the Philippines.